Role of Resilience in the Relationship Between Food Security and Wellbeing - Sh. A. Nurgazy; A. M. Seitkaziyeva; Z. Simanaviciene (Экономика: стратегия и практика)
There are discussions among scientists on how food security and resilience can effect on the psychological wellbeing of university students. The main purpose of this paper is to explore the effect of food security on the psychological wellbeing of university students by examining the mediating role of resilience. The quantitative survey was used to predict that the recipients’ wellbeing would increase when there is a positive effect on food security and resilience. Moreover, it was also expected that ensuring food security, would increase the resilience of the recipients. Questionnaires were used to collect data from more than 180 students from the largest Higher education institutions and one hundred and thirty-six of them were reliable for analysis. Only students were selected to the sample, because they are one of the most vulnerable groups in our society, especially those who come from regions to big cities like Almaty for the first time. Based on the structural modeling of Smart PLS, the results show that resilience mediates the relationship between Food security and psychological wellbeing. Moreover, mediation analyses supported the hypothesized model. This paper contributes to a more complete understanding of how investment in student’s food security may support or build students psychological wellbeing. Additionally, we contribute to the emerging literature on the mediating effect of resilience. Therefore, there is a need to support activities within and outside of government, as well as the effective participation of stakeholders to provide a coordinated and collaborative response.